ATMOSPHERIC AIR AND ITS POLLUTION (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
There can be no life on the globe without oxygen. Oxygen is a product of the vital activity of terrestrial plants, when plants absorb and decompose water and carbon dioxide during photosynthesis, releasing free oxygen into the atmosphere.